Participation of Georgian Local Authorities in the Process of Hospital Care Reforms - Tegetashvili, Ana; Gerzmava, Otar; Makalatia, Ana; Khimshiashvili, Nino (European Scientific Journal, ESJ, 2023)
The article addresses power distribution issues within the context of scientific discourse and explores potential solutions to be implemented by local authorities in the realm of Hospital Care reforms in Georgia, particularly in the conditions of authority decentralization. The significance of addressing this scientific issue stems from the financial challenges faced by many communities, especially in economically depressed Georgian regions. Prior to the reform, the network of hospital facilities relied on subsidies from higher-level budgets. The methodological approach involves the use of desk research, secondary analysis of literary, research, and analytical sources, along with regulatory methods. The research spans from 1991 to 2022, focusing on the power of local self-governments, both their inherent powers and those delegated to them, given that almost 60% of medical services are provided at the territorial community level. The article presents empirical analysis results regarding the distribution of financial power in the new model of Hospital care management. It demonstrates that, fundamentally, the new model remains budget-funded, consistent with the pre-reform structure. The research empirically and theoretically supports the assertion that the overall direction of reforms has been appropriately chosen, a sentiment echoed by positive assessments from international experts. Key conclusions drawn from the research include: Georgia grapples with challenges and inconsistencies between the local self-government reform and medical reform, particularly concerning the decentralization of funding for the basic level of local self-government and inconsistencies in creating hospital districts and altering administrative territorial divisions at the district level. The new model of Hospital care management in Georgia retains a state-funded structure, a fundamental departure from European models that involve a combination of state and insurance funding. The Georgian government is implementing Hospital Care reforms through an evolutionary scenario, progressing through three stages: pilot planning, active reforms, and integration into a unified national model. Local authorities, serving as facility owners and funding agents, play a crucial role. However, further political dialogue is necessary to reconcile decentralized roles and align priorities with the national policy in the field of Hospital care. To stabilize the transformation of the Hospital care system, it is imperative to establish divided ownership for reform implementation among key stakeholders, including local self-governments, service providers, and citizens. United territorial communities have the opportunity to enhance the quality of medical services through the conclusion of cooperation agreements. The findings of the research can be valuable for local authorities representing the interests of territorial communities and for local executive authorities involved in the implementation of these reforms. Additionally, the research aligns with Georgia's commitment to the path towards European integration changes. This process is developing very slowly in Georgia. This is a loss of opportunity to raise the standard of living of local communities.